Breaking Dawn (The Twilight Saga #4) - Stephenie Meyer (Great Britain Atom, 2010)
Now that Bella has made her decision, a startling chain of unprecedented events is about to unfold with potentially devastating and unfathomable consequences. Just when the frayed strands of Bella's life seem to heal and knit together, could they be destroyed forever?
Keywords: Fiction; Paranormal; Young Adult; Fantasy; Romance